Cherry Picking Disability Rights? Swedish Disability Policy on Employment, Health and Participatio - Nouf-Latif, Faten; Andersson, Katarina; Markström, Urban (Nordic Journal of Working Life Studies, 2020)
The aim of this article is to broaden the understanding of how Swedish disability policies are constructed to meet the objectives of the ratified UN Convention on the Rights of Persons with Disabilities (CRPD) regarding active citizenship and full participation on an equal basis with others. The study examines two policy domains: health and employment. Recently issued legal documents are analyzed using the approach of directed content analysis and the theories of ‘social risk’ and ‘governance’. The results suggest that the policy area of employment implicitly and explicitly overshadows the policy area of health and related rights accounted for in the CRPD. A more nuanced perspective in disability policies concerning employment in relation to active citizenry and full participation is required, accompanied by social policy schemes that encompass the perspective of the CRPD as a whole in all support-to- work services, instead of the limited focus of finding full-time employment